1996
DOI: 10.1002/(sici)1097-0290(19960405)50:1<36::aid-bit5>3.0.co;2-2
|View full text |Cite
|
Sign up to set email alerts
|

On-line monitoring of respiration in recombinant-baculovirus infected and uninfected insect cell bioreactor cultures

Abstract: Respiration rates in Spodoptera frugiperda (Sf‐9) cell bioreactor cultures were successfully measured on‐line using two methods: The O2 uptake rate (OUR) was determined using gas phase pO2 values imposed by a dissolved oxygen controller and the CO2 evolution rate (CER) was measured using an infrared detector. The measurement methods were accurate, reliable, and relatively inexpensive. The CER was routinely determined in bioreactor cultures used for the production of several recombinant proteins. Simple linear … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
47
0
1

Year Published

1997
1997
2010
2010

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 117 publications
(52 citation statements)
references
References 50 publications
4
47
0
1
Order By: Relevance
“…Several papers have reported that baculovirus-infected insect cells consume the main nutrients at higher rates than uninfected cells (Sugiura and Amman 1996;Radford et al 1997;Rodas et al 2005). However, other papers have shown that the consumption rates of the main nutrients either do not change (Wong et al 1994;Kamen et al 1996;Palomares et al 2004) or decrease (Rhiel and Murhammer 1995) after baculovirus infection in insect cells. The explanation to these contradictory results could be based on the different experimental conditions (cell line, culture medium, culture strategy, time and multiplicity of infection) that were employed in the cited studies.…”
Section: Discussionmentioning
confidence: 99%
“…Several papers have reported that baculovirus-infected insect cells consume the main nutrients at higher rates than uninfected cells (Sugiura and Amman 1996;Radford et al 1997;Rodas et al 2005). However, other papers have shown that the consumption rates of the main nutrients either do not change (Wong et al 1994;Kamen et al 1996;Palomares et al 2004) or decrease (Rhiel and Murhammer 1995) after baculovirus infection in insect cells. The explanation to these contradictory results could be based on the different experimental conditions (cell line, culture medium, culture strategy, time and multiplicity of infection) that were employed in the cited studies.…”
Section: Discussionmentioning
confidence: 99%
“…The successful application of this technology in a wide variety of cell culture processes is described in the literature. 5,6,9,[13][14][15][16] Several studies report measurements of the permittivity at one single or two frequencies (to reduce the effect of a changing media composition on the signal). Permittivity measurements are described as a tool to directly measure the viable biomass.…”
Section: Introductionmentioning
confidence: 99%
“…However, with current sensor technology, on-line monitoring of the physiological state remains a challenging task, rendering its use as a bioprocess control parameter complex (Konstantinov 1996;Henry et al 2007). Permittivity-based in situ probes are now an established tool for the measurement of biomass in real-time in a wide variety of cell culture processes (Kamen et al 1996;Zeiser et al 1999;Elias et al 2000;Zeiser et al 2000;Ducommun et al 2001Ducommun et al , 2002Cannizzaro et al 2003). Permittivity is a direct measure of the membrane enclosed volume fraction or biovolume of the cell suspension.…”
mentioning
confidence: 99%